Pentamidine rescues contractility and rhythmicity in a Drosophila model of myotonic dystrophy heart dysfunction - Mouli Chakraborty; Estela Selma-Soriano; Emile Magny; Juan Pablo Couso; Manuel Pérez-Alonso; Nicolas Charlet-Berguerand; Ruben Artero; Beatriz Llamusi (The Company of Biologists, 2015)
Up to 80% of individuals with myotonic dystrophy type 1 (DM1) will develop cardiac abnormalities at some point during the progression of their disease, the most common of which is heart blockage of varying degrees. Such blockage is characterized by conduction defects and supraventricular and ventricular tachycardia, and carries a high risk of sudden cardiac death. Despite its importance, very few animal model studies have focused on the heart dysfunction in DM1. Here, we describe the characterization of the heart phenotype in a Drosophila model expressing pure expanded CUG repeats under the control of the cardiomyocyte-specific driver GMH5-Gal4. Morphologically, expression of 250 CUG repeats caused abnormalities in the parallel alignment of the spiral myofibrils in dissected fly hearts, as revealed by phalloidin staining. Moreover, combined immunofluorescence and in situ hybridization of Muscleblind and CUG repeats, respectively, confirmed detectable ribonuclear foci and Muscleblind sequestration, characteristic features of DM1, exclusively in flies expressing the expanded CTG repeats. Similarly to what has been reported in humans with DM1, heart-specific expression of toxic RNA resulted in reduced survival, increased arrhythmia, altered diastolic and systolic function, reduced heart tube diameters and reduced contractility in the model flies. As a proof of concept that the fly heart model can be used for in vivo testing of promising therapeutic compounds, we fed flies with pentamidine, a compound previously described to improve DM1 phenotypes. Pentamidine not only released Muscleblind from the CUG RNA repeats and reduced ribonuclear formation in the Drosophila heart, but also rescued heart arrhythmicity and contractility, and improved fly survival in animals expressing 250 CUG repeats.